'Walking into the rock … ': Labyrinth experience as thin place and [spi]ritual direction. Issue 1 (2nd January 2022) - Daughtry, Phil; Macaitis, Kirsten; Zweck, Tick
ABSTRACT: This article offers findings from a small study of staff and student experiences in a tertiary educational context at Tabor Institute of Higher Education, South Australia. Participants were invited to complete three curated labyrinth walk and reflection activities over a period of three months as an extra-curricular opportunity for experiential spiritual practice. Analysis of the rich narrative data from participants' experiences reveals the potential of the labyrinth ritual to enable transformative insights of significant depth and meaning to individuals. Three of the themes which emerged from the data are presented in this article. The first relates to a heightened sense of the dissolution of individual identity into a greater sense of connectivity or fusion with, and to, elements of nature, such as rock, water, and sand. The second speaks of deep emotional connection and processing of a pivotal, personal historical turn in spiritual awareness. The third relates to a movement into unusual peace, a sense of the living and fluid nature of time and space, and the agency of ritual practice as active and something that is 'at work in the person' rather than passive, with the person doing the work of the ritual. The researchers were struck by two phenomena in the process. Firstly, the poignant efficacy of non-didactic ritual for spiritual education and growth. Secondly, the interactive and dynamic relationship between the desire of the participants for deep experience, the actual practice of the labyrinth walk, and the importance of mindfulness and context-sensitive curation of the events.